The role of the family in a lonely life and works of the modern writer – Jan Rybowicz - Litwicka, Paulina (Zakład Historii Edukacji Instytutu Pedagogiki Uniwersytetu Wrocławskiego, 2013)
The biographical and historical-literary analysis of works of the modern writer Jan Rybowicz indicates that having a family of one’s own was an unreachable dream for the artist, which affected his self-esteem and was a chance for his complete fulfillment. Letters to Elisabeth are showing problems of a sensitive artist in his contacts with women. The selected literary works draw attention at the issues of a lonely man missing a wife and children which he has never had. Autobiographical prose points to the passing time and difficult reality that made having a family impossible for the writer. Jan Rybowicz’s works show a man torn between his wishes and reality. A desire of having his own family gave him the strength to write, but, on the other hand, it made him suffer.
Keywords: Jan Rybowicz; Lisia Góra; Stare Dobre Małżeństwo; family relations; Polish literature; contemporary literature; modern poetry